Kinetic investigation into Ni/CeO2 in dry reforming of methane based on Langmuir-Hinshelwood mechanism - LI Yanan; QIAO Yibing; LIU Peng; XU Haojin; WU Le; WANG Yuqi (Xi'an Gongcheng Daxue xuebao)
Dry reforming of methane could transfer CH4 and CO2 into valuable syngas (H2 and CO), which is employed to synthesize high-value-added methanol, diesel and gasoline through Fischer-Tropsch reaction. According to the experimental date of Ni/CeO2 catalyst, the kinetic correlated parameters of each model based on Langmuir-Hinshelwood mechanism, such as the total rate constant, the adsorption equilibrium constant of CH4 and the adsorption equilibrium constant of CO2, are fitted and determined. Moreover the experimentally determined CH4 conversion rates were compared with the modeled values and analyzed by ANOVA. The kinetic model exhibits the smallest root mean square error (0.045 9) and the residual sum of squares (0.082 2), and the highest R2 (0.984 4), which indicate that this model is the most applicable to Ni/CeO2 for dry reforming of methane. The reaction pathway of Ni/CeO2 for dry reforming of methane contains the following several steps, such as dual-site associative adsorption of both CH4 and CO2, bimolecular surface reaction and dual-site desorption.